The Electromagnetic Environment Analysis of Transmission Engineering in UHVDC Converter Station Based on Computer. Issue 2 (October 2020) - Xie, Lianke; Ma, Xingang; Zhang, Guoying; Guo, Zhaofeng
Abstract: UHVDC conveyance lines and unique advantages play a very special role in the construction of UHV power grid strategy. However, people gradually found that its related electromagnetism condition has become an important factor limiting its future development. At present, the problem of electromagnetic discharge in the living room and the electromagnetic discharge in the living room have aroused the attention of the experts [1] . First, this paper briefly describes the characteristics of UHVDC conveyance technique and the support of main equipment. Then, this paper describes the electromagnetic environment analysis of the UHV DC converter station transmission project based on the computer. Finally, the conclusion is drawn.